A MECHANISM OF THE FORMATION OF DEEP SEDIMENTARY BASINS ON CONTINENTS: THE BARENTS BASIN - Artyushkov E.V. (My University, 2004)
Inside continents and on their edges, deep sedimentary basins such as Caspian, Southern Caspian, Barents, Black-Sea, and other ones exist. Thickness of sediment layers in them are 15 to 20 km and more. According one version of mechanism of forming the basin, tension of lithosphere is reason for arising the basin. According other version of mechanism of forming the basin, rock compaction in lower crust due to phase transition is reason for arising the basin. Formation of Barents basin has been considered. Rocks in the basin have been investigated. Results of the investigations that the main reason of the basin formation is rock compaction.